Letter from Henry D. Rogers to James Curtis Booth, April 20, 1836 - Rogers, Henry D. (Henry Darwin) (1836)
James Curtis Booth (1810-1888) is appointed as Henry Darwin Rogers' (1808-1866) assistant.
Keywords: Booth, James Curtis, 1810-1888; Rogers, Henry D. (Henry Darwin), 1808-1866; Geological Survey (U.S.); Geological Survey of Pennsylvania; Geology